Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/hrm.20014
|View full text |Cite
|
Sign up to set email alerts
|

Technology‐assisted supplemental work: Construct definition and a research framework

Abstract: Extending the workday to the home into the night and weekends is nothing new

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 81 publications
0
101
0
4
Order By: Relevance
“…Kinman and Jones (2008) found that academics who worked during the evenings and on weekends experienced more WLC than academics who did not work after hours. It is therefore not surprising that studies in this field of research have suggested and found a significant relationship between TASW and WLC (Boswell & Olson-Buchanan, 2007;Fenner & Renn, 2010;Fenner & Renn, 2004;Messersmith, 2007). These studies reveal a positive relationship between TASW and WLC.…”
Section: The Consequences Of Tasw and The Relationship With Wlcmentioning
confidence: 92%
See 4 more Smart Citations
“…Kinman and Jones (2008) found that academics who worked during the evenings and on weekends experienced more WLC than academics who did not work after hours. It is therefore not surprising that studies in this field of research have suggested and found a significant relationship between TASW and WLC (Boswell & Olson-Buchanan, 2007;Fenner & Renn, 2010;Fenner & Renn, 2004;Messersmith, 2007). These studies reveal a positive relationship between TASW and WLC.…”
Section: The Consequences Of Tasw and The Relationship With Wlcmentioning
confidence: 92%
“…Supplemental work, as explained by Venkatesh and Vitalari (1992), is a form of distributed work, where full-time individuals work at home after regular working hours or on weekends. According to Fenner and Renn (2004), the concept of supplemental work is not a new phenomenon as individuals often work at home during the evenings and weekends. However, the increased possibility of being able to do so, with the support of ICTs, is regarded as a new phenomenon (Fenner & Renn, 2004;Venkatesh & Vitalari, 1992).…”
Section: Technology-assisted Supplemental Workmentioning
confidence: 99%
See 3 more Smart Citations